Keamanan Energi dan Hubungan Kerja Sama Cina-Jepang - Sagena, Uni Wahyuni; Moorthy, Ravichandran (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2012)
This article explores the Chinese and Japanese energy relationship by describing changes in the Chinese energy situation as a starting point. The article breaks down that the strength of the Chinese domestic energy since the 1970s and the decade of the 1980s make the countryâs independent in energy and become the largest oil exporter country, especially to the energy poor neighbor, Japan. However, entering the decade of the 1990s or the end of the post-Cold War era, the situation changed drastically when China faces the energy crisis. The change status bring a wide range of implications for Japan and influence the bilateral energy relations of the two countries, which tend to be ambivalent or ambiguous, between energy cooperation and the potential of conflict. As main purpose of this paper is to identify which energy issues are a direct influence on the behavior of the interaction between China and Japan and as knowledge contribution in understanding the issues of energy itself and the Sino-Japanese relations as a whole. The main assumption of this article is that the energy security factor is a very important issue and significant in shaping the nature and pattern of Sino-Japanese relations, because it raises consideration of national interests and national security of both countries, particularly in the present and the future.